Studi Komparatif Peraturan Adopsi Anak Di Negara Indonesia dan Palestina - Sakila, Yola Cindytia; Maulidia, Rohmah (Sakina: Journal of Family Studies, 2023)
This research aims to determine the regulations for child adoption in Indonesia and Palestine and analyze the problems of child adoption in Indonesia and Palestine. This research uses library research by collecting qualitative data. This data was obtained from several sources such as books, journals and the internet. This research uses a normative approach by analyzing the regulations in Muslim countries, namely Indonesia and Palestine, which relate to the law on adoption or placement of children. The results of this research are that adoption regulations in Indonesia and Palestine both guarantee the welfare of children, but prohibit adopted children from being given the status of biological children and having the fate of their adoptive father. The difference is, in Indonesia it is permissible for single parents to adopt, but in Palestine it must be a husband and wife pair. In Indonesia there is only 1 home visit when a child is being adopted, in Palestine there are 2 home visits, namely pre and post adoption, in Indonesia there is an explanation of the age that is considered a child, in Palestine there is none. However, due to the prolonged conflict situation, namely the aggression launched by Israel against Palestine, Palestine has tightened its regulations on adopting children, namely not allowing Palestinian children to be accepted and taken to other countries. Adoption is permitted only to support living and education costs.Keywords: Regulations, Child Adoption, Indonesia and Palestine